2019
DOI: 10.1039/c8ra06493h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of super-hydrophilic polyphenylsulfone nanofiber membranes for water treatment

Abstract: A 3-dimensional nanofiber membrane with superior hydrophilicity and mechanical properties significantly improves flux and salt rejection in thin film forward osmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…The selective layers of previously reported ABMs were prepared by directly fusing or collapsing AQPs-incorporated liposomes onto porous substrates or membrane surfaces. [17][18][19] However, most of the membranes fabricated by this method exhibit relatively low NaCl retention, which renders them unusable for forward osmosis due to draw-solute loss and low feed-solute rejection. Maintaining the activity of AQPs in the external environment and reducing defect formation in the selective layer remain challenging tasks in the preparation of high-performance ABMs.…”
Section: Introductionmentioning
confidence: 99%
“…The selective layers of previously reported ABMs were prepared by directly fusing or collapsing AQPs-incorporated liposomes onto porous substrates or membrane surfaces. [17][18][19] However, most of the membranes fabricated by this method exhibit relatively low NaCl retention, which renders them unusable for forward osmosis due to draw-solute loss and low feed-solute rejection. Maintaining the activity of AQPs in the external environment and reducing defect formation in the selective layer remain challenging tasks in the preparation of high-performance ABMs.…”
Section: Introductionmentioning
confidence: 99%
“…PPSU membrane samples were systematically subjected to low-pressure or atmospheric-pressure plasma treatment. SEM images before and after plasma treatment revealed that plasma treatment induced no significant morphological changes of the porous network [34]. Plasma parameters are listed in Table 1, and XPS acquired element compositions are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases the nanofibrous membranes are coated with another material providing specific properties, e.g. nanofibrous PPSU membranes have been coated with Aquaporin [34], which is hydrophilic and thus requires a hydrophilic PPSU surface. Aquaporin is a water channel protein that provides selective conduits for water with a high osmotic permeability [45, 46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ZIF-8 as a hydrophobic additive promotes the "deswelling effect" as the membrane pores are retained at their size, allowing more liquid to pass through without absorbing too much water, thus reducing membrane swelling. Usually, hydrophilic materials swell in water as water forms physical interactions with the material [38]. Due to this reason, the superhydrophilic membrane is sometimes not preferable to be used since it has greater water uptake, and therefore greater swelling effect.…”
Section: Membrane Porosity and Surface Roughnessmentioning
confidence: 99%